417 Can myocardial stiffness measurements distinguish the underlying pathology in hearts with thick walls? A shear wave imaging study using ultra-high frame rate echocardiography. (17th January 2020) - Cvijic, M; Bezy, S; Petrescu, A; Santos, P; Orlowska, M; Chakraborty, B; Duchenne, J; Pedrosa, J; Vanassche, T; Delforge, M; Van Cleemput, J; Dhooge, J; et al.
Abstract: Background: Different pathophysiologic pathways in the development of left ventricular (LV) hypertrophy may alter passive myocardial stiffness differently. Recently, cardiac shear wave (SW) elastography has been proposed as new non-invasive technique for assessing myocardial stiffness. Purpose: To explore the relationship between myocardial stiffness and the underlying pathological substrates for cardiac hypertrophy. Methods: We included 17 patients with cardiac amyloidosis (AML) (69 ± 10 years, 41% male), 17 patients with hypertrophic cardiomyopathy (HCM) (59 ± 16 years, 65% male) matched for interventricular septum (IVS) thickness and 17 hypertensive patients (HT) with prominent myocardial remodelling (56 ± 15 years, 71% male). LV parasternal long axis views were acquired with an experimental ultrasound scanner at 1255 ± 354 frames per seconds. Myocardial acceleration maps were created from the HFR-datasets and an anatomical M-mode line was drawn along the midline of the IVS (Figure A). The propagation velocity of natural SWs occurring at mitral valve closure (MVC) was measured on these M-modes in order to assess operating myocardial stiffness. To compare myocardial stiffness among hearts with differing loading conditions and chamber geometry, SW velocities were normalized to operating end-diastolic wall stress. The end-diastolic wall stress was estimated at the IVS from regional wall thickness, longitudinal and circumferential regional radii of curvature, and noninvasively estimated left ventricular end-diastolic pressure (EDP). Results: IVS thickness was significant different among groups (AML: 1.63 ± 0.33 cm, HCM: 1.69 ± 0.21 cm, HT: 1.48 ± 0.14 cm; p = 0.037). HT patients had significant higher septal radius of curvature compared to other two groups (p < 0.05), while the AML patients had the highest estimated EDP (p < 0.05). All groups had comparable, elevated SW velocities at MVC (AML: 6.49 ± 1.00 m/s, HCM: 6.46 ± 1.45 m/s, HT: 6.22 ± 0.96 m/s; p = 0.752). Considering end-diastolic wall stress, HT patients had the same SW velocity at higher wall stress compared to AML and HCM (Figure B), indicating lower myocardial stiffness in the HT group. SW velocities normalized for wall stress indicated significantly different myocardial stiffness among groups (p = 0.003) (Figure C). The HT group had the lowest normalized myocardial stiffness, whereas values of the AML group overlapped with the HCM group (p = 1.00). Conclusions: Our study demonstrated that shear wave elastography can detect differences in myocardial stiffness in hearts with thick walls. Considering the effect of wall stress, our results suggest that factors other than chamber geometry and loading condition mediate myocardial stiffness in hearts with thick walls. We hypothesize that differential changes in cardiomyocytes and/or the extracellular matrix contribute to the differential myocardial stiffening in different pathologic entities of LV hypertrophy.